Small signal synchronization stability of hybrid synchronization based DC voltage control with different inner control loops - Rongcai Pan; Xiaobing Liang (Scientific Reports)
Abstract Hybrid synchronization based DC voltage control (HS-DVC) with phase locked loop is claimed to perform well in strong grid compared with traditional grid forming based DC control (GFM-DVC) for renewable energy sources (RESs). However, the small signal synchronization stability of HS-DVC with different inner control loops is less analyzed in the previous literatures. To fill this gap, the small signal synchronization stability of HS-DVC with different inner control loops is investigated and the stability enhancement is unveiled in this article. A closed loop model focusing on the synchronization loop is proposed, i.e., the synchronization unit is seen as the controller, and the inner control loop, reactive power loop and power stage are seen as the plant. With the proposed model, synchronization stability of HS-DVC under three different inner control loops, cascaded voltage current loop, single voltage loop and voltage magnitude phase loop (referred to as type i, ii, and iii) can be evaluated in one frame work. Four insights about HS-DVC proposed in this article are revealed. The larger inertia constant deteriorates the system stability of traditional GFM-DVC and HS-DVC is stable with relatively large inertia constant. Compared with HS-DVC with only AC and DC voltage synchronization in the previous work, the HS-DVC in this work with inclusion of active power synchronization has a better stability. Compared with type i and type ii based inner control loops, the type iii based inner control loop is easier to be stable. Unlike the DC voltage equivalent RESs, DC current equivalent RESs introduce right half plane poles in the plant and the stability becomes worse in weak grid with DC current equivalent RESs. Electromagnetic transient (EMT) simulations with Simulink are performed out to verify the analysis.